Internal Control, Love of Money, Individual Morality, and Information Asymmetry: Influences on Accounting Fraud Tendency - I Kadek Feri Mahardika; A.A. Gde Putu Widanaputra (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
The objective of this study is to examine the impact of internal control, individual morality, information asymmetry, and love of money on the propensity for accounting fraud at PT. Bali Regional Development Bank, Badung Branch Office. A sample of 44 respondents was selected using purposive sampling technique. The data analysis method employed is Partial Least Square (PLS), which includes bootstrapping, internal model evaluation, and external model evaluation. The findings demonstrate that internal control and individual morality negatively impact the propensity for accounting fraud. Conversely, love of money and information asymmetry positively influence this propensity.